Massive hemopericranium following trivial trauma in a child with hypofibrinogenemia: A case report and review of the literature - Rajeev Sharma; Laxmi Naraian Gupta (Indian Journal of Neurosurgery)
Subgaleal hematoma is a potentially life-threatening extracranial bleed that occurs most commonly in neonates after difficult instrumental deliveries. Its occurrence beyond the neonatal period is rare and is often associated with head trauma involving tangential or radial forces applied to the scalp causing emissary veins traversing the subgaleal space to be ruptured. Large progressive subgaleal hematoma due to trivial head trauma in a 5-years-old child of hypofibrinogenemia with no reported literature is interesting to describe.